Fertigación del cultivar banano musa sapientum en un sistema de riego por aspersión subfoliar en Arenillas El Oro - Amaya Delgado, Washington Antonio (2011)
The research was conducted in the Banana Industry Hacienda Santa Maria owned by Mr. Angel Andrade, located on the road jumon - St. Augustine, Florida site belonging to the canton Arenillas, El Oro province, region 7, for this study were raised following objectives: 1.-Determining the best dose of fertilizer using fertigation in banana cultivation, 2.-To establish the dose and timing of irrigation, 3.-establish the quality and yield of banana and 4.-economic analysis based fertilizer and production. The treatments with the prior selection and labeling was performed on the mother plants were selected per plot 60 children, aged between 8 and 10 weeks, which presented the best botanical characteristics, physiological and location relative to the mother, identifying them with paint and assigning a number which was written in the pseudostem of the mother plant, these numbers corresponded to the number of plant. And as subsequently developed the children selected, the identification was changed using a cardboard card. The design used to study the effects of fertigation was that of randomized blocks with four treatments and three replications. The variables evaluated were: plant height, pseudostem diameter, week after flowering, plant age at flowering, plant age at harvest, bunch weight, bunch length, number of hands per bunch, number of fingers per bunch, weight of the spine, hands and distances between boxes processed. The analysis of variance and Duncan test at 5% probability were statistically significant for most variables, giving better treatment as the provision of irrigation for a period of 02h30 more fertilizer input, differing from the others despite they also achieved significant results in research.